PENINGKATAN EFISIENSI OPERASIONAL PENGELOLAAN HOMESTAY DI PULAU BOKORI MELALUI PELATIHAN MANAJEMEN OPERASI SEDERHANA - Hatani, La; Palilati, Alida; Patwayati, Patwayati; Yusuf, Yusuf; Usman, Usman (Jurnal Pengabdian Masyarakat Sabangka, 2025)
The main objective of this training is to provide basic knowledge and skills in operations management for homestay managers on Bokori Island. This community service activity uses a participatory-educational approach through the stages of observation, material preparation, implementation, and evaluation. The training was attended by 25 homestay managers and village officials, and took place with high enthusiasm and active participation. The evaluation results showed a significant increase in the participants' abilities, where 80% were able to understand and compile daily operational work procedures, while 70% began to implement simple bookkeeping using the provided format. Participants also increasingly understood the importance of efficiency in managing time, energy, and costs. The materials presented included an introduction to homestay operations management, work schedule preparation and customer service, guest recording and simple financial reports, and simulations of stock management and room cleanliness. Overall, this training succeeded in improving the participants' abilities in optimizing the operational efficiency of homestays on Bokori Island